Perilaku fertiliti dalam kalangan wanita pribumi Sabah Dan Sarawak - Ubong Imang; Ali Akbar Gulasan; Dayang Suria Haji Mulia; Marsitah Mohd Radzi; Mustapa Abd Talip (Universiti Malaysia Sabah, 2012)
No abstract